Ground Displacements Estimation through GNSS and Geometric Leveling: A Geological Interpretation of the 2016–2017 Seismic Sequence in Central Italy - Riccardo Salvini; Claudio Vanneschi; Chiara Lanciano; Renzo Maseroli (Geosciences)
Between August 2016 and January 2017, a very energetic seismic sequence induced substantial horizontal and vertical ground displacements in the Central Italian Apennines. After this event, the Italian Military Geographical Institute (IGM), owner and manager of the Italian geodetic networks, executed several topographic surveys in the earthquake area in order to update the coordinates of vertices belonging to the IGM95 geodetic network. The measurements began in the areas where the most significant deformation occurred: the localities of Amatrice and Accumoli, in the Rieti Province, and the area covering Norcia and Castelluccio, in the Province of Perugia, all the way to Visso (Province of Macerata). The activities described in this paper focused on the updated measurement of the IGM95 network points through GNSS and the restatement of extensive parts of the high precision geometric lines that were levelled until reaching stable zones. This unprecedented amount of data was used for a new geological interpretation of the seismic sequence, which confirms some of the previous hypotheses of the scientific community. In the analyzed territory, the latest estimate of the geodetic position points has allowed for an accurate determination of the east and the north and of the altitude components of the displacement induced by the earthquake through a comparison with the previous coordinates. The results confirm that the seismicity was induced by normal faults system activity. Still, they also indicate the possible influence of a significant regional thrust that conditioned the propagation of the seismicity in the area. The obtained maps of the displacement are coherent with other geodetic works and with a rupture propagation driven by the documented geotectonic structure.